Isolation and characterization of monoclonal antibodies against human carbonic anhydrase-IX. Issue 1 (1st January 2021) - Lenferink, Anne E.G.; McDonald, Paul C.; Cantin, Christiane; Grothé, Suzanne; Gosselin, Mylene; Baardsnes, Jason; Banville, Myriam; Lachance, Paul; Robert, Alma; Cepero-Donates, Yuneivy; Radinovic, Stevo; Salois, Patrick; et al.
ABSTRACT: The architectural complexity and heterogeneity of the tumor microenvironment (TME) remains a substantial obstacle in the successful treatment of cancer. Hypoxia, caused by insufficient oxygen supply, and acidosis, resulting from the expulsion of acidic metabolites, are prominent features of the TME. To mitigate the consequences of the hostile TME, cancer cells metabolically rewire themselves and express a series of specific transporters and enzymes instrumental to this adaptation. One of these proteins is carbonic anhydrase (CA)IX, a zinc-containing extracellular membrane bound enzyme that has been shown to play a critical role in the maintenance of a neutral intracellular pH (pHi ), allowing tumor cells to survive and thrive in these harsh conditions. Although CAIX has been considered a promising cancer target, only two antibody-based therapeutics have been clinically tested so far. To fill this gap, we generated a series of novel monoclonal antibodies (mAbs) that specifically recognize the extracellular domain (ECD) of human CAIX. Here we describe the biophysical and functional properties of a set of antibodies against the CAIX ECD domain and their applicability as: 1) suitable for development as an antibody-drug-conjugate, 2) an inhibitor of CAIX enzyme activity, or 3) an imaging/detection antibody. The results presented here demonstrate the potential of these specific hCAIX mAbs for further development as novel cancer therapeutic and/or diagnostic tools.